An instrumental analysis of diphthongs in Malaysian English / Lim See Yin - Lim, See Yin (2014)
This paper demonstrates an instrumental analysis of Diphthongs in Malaysian English (MalE) diphthongs. The establishment of comparison between MalE and Singapore English (SgE) was made with an aim to investigate if there were any significant differences between all the diphthongs of both, the postcolonial Englishes which are now at different phases. Specifically it addresses the following research questions: (1) This study aims to examine the qualities of English diphthongs produced by Malaysian English and Singapore English speakers. (2) To what extent are English diphthongs produced similarly in Malaysian English and Singapore English? In order to address these questions, data was recorded with a total of twenty female speakers from both Malaysia and Singapore to establish a valid comparison. Two groups of respondents consisting five Malay and five Chinese undergraduates aged 18 to 26 each were recruited to do a voice recording. A total of 20 participants completed 2 tasks. Task 1: Each respondent recited a word list of the embedded tokens which contains the eight diphthongs (Bayed /beId/, Bode /b@Ud/, Bide /baId/, Boyd /bOId/, Bout /baUt/, Beard /bI@d/, Bear /be@(r)/, Poor /pU@(r)/). Task 2: A picture was given as an instrument to prompt the respondents on the target words which contained the eight diphthongs in the natural connected speech via an interview. With the audio files recorded, waveforms and spectrograms of the files were generated using PRAAT. Based on the data analysis and examinations of the waveforms and spectrograms of the selected words, the first two formants (F1 and F2) of the vowel pairs were identified. The values were subsequently averaged and converted to the auditory Bark scale and thus graphs of F1-F2 in Bark were plotted for both MalE and SgE to enable comparisons in terms of the acoustic descriptions. iv The findings suggest that both MalE and SgE have all the eight diphthongs. However, there is a great deal of variations in the production of all the diphthongs for both MalE and SgE. Generally, Singaporean speakers produce all the diphthongs with a greater diphthongal movement compared to Malaysian speakers. Monophthongization is reported in /@U/ of MalE in Task 2 which involves the natural speech during the interview. /e@/ of MalE is also found to have the smallest diphthongal movement in Task 1 which involves the citation word, Bear. The findings presented in this paper are preliminary in nature. Thus, the researcher hopes it makes a small contribution to the growing body of research in the context of production of diphthongs in these two varieties of English.